Dogeaters - Hagedorn, Jessica Tarahata 1949- (Contemporary American fiction, 1991)
The destinies of a varied group of characters--movie stars, department store clerks, the wealthiest man in the Philippines--are intertwined with a beauty pageant, a film festival, and an assassination, in a study of the Philippines under Marcos.